2023
DOI: 10.3389/fsurg.2023.1138805
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric analysis of the scientific production on inguinal hernia surgery in the web of science

Abstract: ObjectivesTo describe the bibliometric characteristics of the world scientific production in inguinal hernia surgery using the Web of Science Core Collection (WoS) database.Materials and methodsA search for original articles published in the WoS up to December 2021 was carried out. Bibliometric analysis was performed using the Bibliometrix data package in R and VOSviewer, version 1.6.17.ResultsA total of 3,795 articles were identified in the database, with an annual average of 81 published articles and sustain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
(30 reference statements)
0
0
0
Order By: Relevance
“…For example, these methods have been used to demonstrate the evolution of keywords related to Enhanced Recovery After Surgery (ERAS) protocols and the most influential authors, institutions and journals in the field over a period of 20 years [17]. Similar analyses have been performed on the topic of inguinal and ventral hernias to demonstrate the most influential authors and journals within the fields [7][8][9]18]. One such analysis recently identified the Ventral Hernia Working Group publication as the second most frequently cited paper on the topic of incisional hernias and found that "acellular dermal matrix" was one of the top 20 keyw ords with the strongest citation bursts after 2010 [8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, these methods have been used to demonstrate the evolution of keywords related to Enhanced Recovery After Surgery (ERAS) protocols and the most influential authors, institutions and journals in the field over a period of 20 years [17]. Similar analyses have been performed on the topic of inguinal and ventral hernias to demonstrate the most influential authors and journals within the fields [7][8][9]18]. One such analysis recently identified the Ventral Hernia Working Group publication as the second most frequently cited paper on the topic of incisional hernias and found that "acellular dermal matrix" was one of the top 20 keyw ords with the strongest citation bursts after 2010 [8].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible to investigate the effect of certain publications on the future scientific evaluation of key terms utilized in these sponsored publications by utilizing bibliometric analysis. Popular uses for bibliometric analyses include the identification of topical trends and identification of the most influential authors and papers within a field [7][8][9].In 2010, the Ventral Hernia Working Group (VHWG) published a classification system to grade incisional hernias based on patient risk factors for wound complications which was funded by LifeCell (LifeCell Corp, Branchburg, NJ, USA), a company that markets biologic mesh [10]. In acknowledgement of a lack of high quality data and existing grading system for evaluating patient risk factors in ventral hernia repair, the group developed a 4-level grading…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, our study focused solely on the SCI-Expanded in WoSCC database, which may have potentially excluded relevant studies, although WoSCC database is the most commonly used database in bibliometrics. [102][103][104][105] Secondly, some high-quality studies published recently may have been underestimated in our analysis due to their limited citation frequency. Finally, due to the constantly updating nature of databases, the dataset for this year is still incomplete and therefore not included in this study.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…This value is comparatively lower than the NTCs recorded for the other papers featured in Table 7. This measure helps account for variations in citation practices across different disciplines and offers a more meaningful basis for comparing citation impact [35]. The NTC metric aims to give equal credit for citations to all of the authors of the paper while accounting for the average citations per document recorded in the database for the year in which the paper was published [36].…”
Section: Paper Analysismentioning
confidence: 99%